1974
DOI: 10.1002/1097-0142(197405)33:5<1325::aid-cncr2820330517>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Plasma prolactin and breast cancer

Abstract: Using a homologous radioimmunoassay we have compared plasma prolactin concentrations in 49 patients with breast cancer and 39 hospital controls. When a drug history was taken into account no difference was found. In addition we have studied the effect of Stilbestrol in 6 females with advanced breast cancer. Remission of disease has been noted in the face of elevated prolactin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In two of these studies, a significant positive association was reported (7,73); no association was observed in two others; and in one a significant inverse association was seen (72). Finally, in four small studies in which premenopausal and postmenopausal women were combined (69,(75)(76)(77), no significant associations were reported. Overall, results from the casecontrol studies have been inconsistent.…”
mentioning
confidence: 94%
“…In two of these studies, a significant positive association was reported (7,73); no association was observed in two others; and in one a significant inverse association was seen (72). Finally, in four small studies in which premenopausal and postmenopausal women were combined (69,(75)(76)(77), no significant associations were reported. Overall, results from the casecontrol studies have been inconsistent.…”
mentioning
confidence: 94%
“…A tendency for women with breast cancer to secrete more growth hormone in response to a glucose load has been described by Greenwood, James, * Meggitt, Miller, and Taylor (1968) and Pearson, Llerena, Samaan, and Gonzales (1968), and recently * Murray, Mozaffarian, and Pearson (1972) have also reported increased levels of circulating prolactin in this disease. In our experience the growth hormone response to insulin hypoglycemia was normal in women with advanced malignancy of the breast (Stewart, Benson, Roberts, Forrest, and Greenwood, 1971) Wilson, and Forrest, 1973;Wilson et al, 1973). Recent results using a homologous assay are shown in the table.…”
Section: Human Breast Cancermentioning
confidence: 81%
“…A tendency for women with breast cancer to secrete more growth hormone in response to a glucose load has been described by Greenwood, James, * Meggitt, Miller, and Taylor (1968) and Pearson, Llerena, Samaan, and Gonzales (1968), and recently * Murray, Mozaffarian, and Pearson (1972) have also reported increased levels of circulating prolactin in this disease. In our experience the growth hormone response to insulin hypoglycemia was normal in women with advanced malignancy of the breast (Stewart, Benson, Roberts, Forrest, and Greenwood, 1971) and circulating prolactin, estimated either by with benign disease of the breast, and those with (Forrest, 1972;Boyns, Cole, Griffiths, Roberts, Buchan, Wilson, and Forrest, 1973;Wilson et al, 1973). Recent results using a homologous assay are shown in the table.…”
Section: Human Breast Cancermentioning
confidence: 91%